Effects of Lowering Cerebrospinal Fluid Pressure on the Shape of the Peripapillary Retina in Intracranial Hypertension - Sibony, P.; Kupersmith, M. J.; Honkanen, R.; Rohlf, F. J.; Torab-Parhiz, A. (Investigative ophthalmology & visual science, 2014)
To analyze the deformations of the peripapillary retinal pigment epithelium-basement membrane (ppRPE/BM) layer in response to procedures that lower intracranial pressure (ICP). Second, to demonstrate how shape changes may complement the mean retinal nerve fiber layer (RNFL) thickness as a measure of intracranial hypertension (ICH) and papilledema. We used geometric morphometrics on spectral-domain optical coherence tomography images to analyze shape change of the ppRPE/BM layer after several interventions that lower cerebrospinal fluid (CSF) pressure. We also evaluated the effects of pressure-lowering interventions on both the anterior-posterior displacement of ppRPE/BM and the mean RNFL thickness. Forty-one patients with ICH and papilledema were studied before and after lumbar puncture (20), CSF shunt (9), and medical treatment of idiopathic ICH (23). We also compared the shape of 30 normal subjects to 23 patients whose papilledema resolved after medical treatment. The ppRPE/BM-layer in ICH and papilledema is characterized by an asymmetric anterior deformation that moves posteriorly and becomes more V-shaped after each pressure-lowering intervention. The differences were statistically significant for all three groups. These shape changes also occur in patients with ongoing ICH who have secondary optic atrophy (without papilledema). Posterior displacement at the margin of the ppRPE/BM layer correlated strongly with overall shape changes. The subsurface contour of the ppRPE/BM layer is a dynamic property that changes with CSF pressure-lowering interventions. It can supplement the RNFL thickness as an indirect gauge of ICP and is particularly helpful in patients with secondary optic atrophy. Direct measurements of displacement at the basement membrane opening may serve as a more convenient office-based surrogate for shape analysis.